Propriedades morfológicas e estruturais e rendimento quântico de geração de radicais hidroxila em amostras sintetizadas de dióxido de titânio - Batista, Paulo dos Santos (2010)
In the present study employed three different methods of synthesis (sol-gel, macroemulsion, precipitation of titanium dioxide by hydrolysis of titanium tetraisopropoxide solvated in different monoalcohols) aiming to obtain photoactive nanomaterials based TiO2. The samples obtained were characterized by instrumental techniques that allowed us to estimate the specific surface area (BET), structure (XRD), the band gap (DRS) and morphology (SEM-FEG). The powders of TiO2 obtained using sol-gel method and macroemulsion generated different distributions of polymorphic materials. The introduction of modifier ions induces the formation of secondary phases, formation of aggregates dispersed on the surface of the particles, and increased the photoactivity of these materials. The synthesis based on precipitation of TiO2 by hydrolysis of titanium tetraisopropoxide solvated by different monoalcohols led to the formation of TiO2 microspheres with different sizes, which showed its interior filled with nanospheres. The polymorph anatase was the main crystalline phase found in powders obtained by this method. The crystallite sizes of anatase ranged from 19 nm to 28 nm, and the average size of nanospheres was 25 nm. The photoactivity of the synthesized TiO2 was estimated by its ability in photogenerate hydroxyl radicals (OH●). The estimated ΦOH● was correlated with the specific surface area of the fraction of anatase polymorph found in the different synthesized TiO2. From this parameter, it was possible to establish a connection between the production method of TiO2 and its apparent photocatalytic action. Between the synthesized oxides, the most promising, based in this parameter, was the obtained by hydrolysis of titanium tetraisopropoxide solvated in 2-propanol, which presented ΦOH● = 4,3%, the value closest to the estimated for TiO2 P25 (6,0%) in the series of synthesized oxides. The simplification of the stages of synthesis and minimizing the consumption of reagents to obtain photoactive TiO2 aiming its use in heterogeneous photocatalysis and systems for converting solar energy into electricity, were strategies employed in this work.